THE METHOD OF MORAL EDUCATION IN CONSTRUCTING PERSONALITY ACCORDING TO ISLAM - Riza Ashari (Universitas Muhammadiyah Ponorogo, 2017)
Nowadays, the moral degradation of muslim young generation is really in a sad matter. However, various negative effects coming from outer part, has caused moral crisis till brought this generation fallen into the depths of misery. For the sake of facing and challenging the negative influence of new century with all its sophisticated of its technology and its development, and to make this generation awake from this backwardness, moral education become the single way and solution which must be gone through to construct Islamic personality. That’s way the writer saw it was so important one to discuss about the method of moral education in constructing personality according to Islam.